(untitled) (International Journal of Management and Sustainability, 2016)
This study examined the valuation of financial performance from 13 Indonesia Estate Firms. The valuation involves eight key performance indicators which are based on accounting principles including Return on Equity, Return on Investment, Total Asset Turnover, Cash Ratio, Current Ratio, and others. Those indicators are combined with indicators weighted to be as Financial Health Score. Both the indicators could be improved simultaneously, but whether the improvement always valuable or not? To answer this question, Economic Value Added (EVATM) was employed to measure shareholder value. Financial reports of 13 firms from the period of 2002 to 2011 are selected. Nine hypotheses were proposed to examine the relationship between performance indicators and financial health score to EVATM. Each hypothesis was tested under Seemingly Unrelated Regression (SUR) model. The findings indicate that all tested hypotheses show significant relationship. However, it can be identified that the creation of financial performance based on accounting method, it would disclose the shareholder value. But EVATM method demonstrates that actually some companies suffer a loss of their value although the financial performance improved.